Eight-year longitudinal falls trajectories and associations with modifiable risk factors: evidence from The Irish Longitudinal Study on Ageing (TILDA). (29th March 2023) - Hartley, Peter; Forsyth, Faye; O'Halloran, Aisling; Kenny, Rose Anne; Romero-Ortuno, Roman
Abstract: Background: The label 'faller' and the associated stigma may reduce healthcare-seeking behaviours. However, falls are not inevitably progressive and many drivers are modifiable. This observational study described the 8-year longitudinal trajectories of self-reported falls in The Irish Longitudinal Study on Ageing (TILDA) and studied associations with factors, including mobility, cognition, orthostatic hypotension (OH), fear of falling (FOF) and use of antihypertensive and antidepressant medications. Methods: Participants aged ≥50 years at each wave were categorised by whether they averaged ≥2 falls in the previous year (recurrent fallers) or not (≤1 fall). Next-wave transition probabilities were estimated with multi-state models. Results: 8, 157 (54.2% female) participants were included, of whom 586 reported ≥2 falls at Wave 1. Those reporting ≥2 falls in the past year had a 63% probability of moving to the more favourable state of ≤1 fall. Those reporting ≤1 fall had a 2% probability of transitioning to ≥2 falls. Besides older age and higher number of chronic conditions, factors that increased the risk of transitioning from ≤1 fall to ≥2 falls were lower Montreal Cognitive Assessment score, FOF and taking antidepressants. Conversely, male sex, higher timed up and go time, the presence of OH and being on antidepressants reduced the probability of improving from ≥2 falls to ≤1 fall. Conclusion: The majority of recurrent fallers experienced favourable transitions. Improvements in cognitive and psychological status, psychotropic prescribing, mobility and OH may help improve trajectories. Findings may help combat stigma associated with falling and promote preventative healthcare-seeking behaviours.